Global usability - Douglas, Ian; Liu, Zhengjie (Springer, 2011)
The concept of usability has become an increasingly important consideration in the design of all kinds of technology. As more products are aimed at global markets and developed through internationally distributed teams, usability design needs to be addressed in global terms. Interest in usability as a design issue and specialist area of research and education has developed steadily in North America and Europe since the 1980?s. However, it is only over the last ten years that it has emerged as a global concern. Global Usability provides an introduction to the important issues in globalizing design and an insight into the development of usability expertise around the world. The book is divided into two sections. The first section deals with the general issues in cross-cultural design and the methods for conducting usability design and evaluation across geographical boundaries. The second section describes the state of usability development in fifteen countries. The descriptions include a history and review of activities and include some unique perspectives that have developed in relation to usability work. Researchers and practitioners from a variety of design-related disciplines will find the book a useful guide for understanding the issues and an excellent reference source for working in any of the countries covered.